Past tense, future sense : competing through creativity : 80 years of design at Philips. - Marzano, Stefano, ....- (Amsterdam : Bis, 2005)
Celebrating the 80th anniversary of design at Philips, Past Tense, Future Sense is a highly visual book presenting an analysis and history of design at Philips. This objective, authoritative and richly-illustrated book gives a fascinating insight into the creation of some of the most iconic products of the past decades. Engaging topics like the rise of design, the role of visionary projects and what actually constitutes good design are discussed at length and vividly brought to life by numerous case studies. In this way Past Tense, Future Sense is a compelling reflection of the remarkable journey undertaken by design, Philips and society during the most extraordinary period our planet has ever witnessed. It will be enjoyed by anyone who appreciates the value of design - not only designers and design historians but by anyone interested in an insiders view of how the diverse range of Philips products come about. For the more futuristically minded, it also offers a glimpse of the sorts of things that may lie ahead. And managers, designers and design professionals may find the history of the design function at Philips interesting as a microcosm of the history and growth of industrial design in general.
Keywords: Industriële vormgeving